School-based outdoor education and teacher subjective well-being: An exploratory study - Deschamps, Antoine; Scrutton, Roger; Ayotte-Beaudet, Jean-Philippe (Frontiers in Education, 2022)
Can school-based outdoor education (OE) benefit teachers’ well-being? Multiple studies have reported the positive impact of OE on students’ well-being and the benefits of contact with nature for adults. However, a literature review revealed no research on the impact of OE on teachers’ well-being. This study explores the possible relationships between OE and preschool and primary school teachers’ subjective well-being (SWB) in Québec, Canada, during COVID-19. A survey measuring teacher SWB was conducted; 381 teachers responded, 164 practiced OE, and 217 did not. The questionnaire results indicated that teachers who practice OE have significantly higher SWB than their colleagues (d = 0.21 to d = 0.36). However, only a limited positive correlation was found between teacher SWB and the number of times teachers practice OE (rho = 0.184). This study suggests that school-based OE is positively related to teacher SWB and therefore has the potential to benefit teachers and students alike.